2018
DOI: 10.1111/jre.12541
|View full text |Cite
|
Sign up to set email alerts
|

Culture‐expanded mesenchymal stem cell sheets enhance extraction‐site alveolar bone growth: An animal study

Abstract: Mandibular marrow-derived MSCs can be fabricated into cell sheets and autogenous transplantation of MSC sheets onto the subperiosteal buccal alveolar bone surface at the tooth-extraction site may increase local bone density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…15,39 All these characteristics have made Al-BMSCs potentially more desirable for wide therapeutic applications. Although it has been found that Al-BMSCs sheet would increase local bone density when transplanted into the tooth-extraction site, 16 the function of Al-BMSCs sheet in vitro and the craniofacial bone defect repairment features in vivo remain unclear. Our results showed that Al-BMSCs sheet have the similar histology structure, higher osteogenic differentiation capacity and bone defect reconstruction in rabbit calvarial defect model, demonstrating Al-BMSCs sheet based tissue regeneration would be a promising strategy for craniofacial defect repair in future clinical applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,39 All these characteristics have made Al-BMSCs potentially more desirable for wide therapeutic applications. Although it has been found that Al-BMSCs sheet would increase local bone density when transplanted into the tooth-extraction site, 16 the function of Al-BMSCs sheet in vitro and the craniofacial bone defect repairment features in vivo remain unclear. Our results showed that Al-BMSCs sheet have the similar histology structure, higher osteogenic differentiation capacity and bone defect reconstruction in rabbit calvarial defect model, demonstrating Al-BMSCs sheet based tissue regeneration would be a promising strategy for craniofacial defect repair in future clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…15 It has also been found that Al-BMSCs can be induced to cell sheets, and can increase local bone density when transplanted into the tooth-extraction site. 16 However, although several studies have compared the character of Al-BMSCs and BMSCs in vitro and in vivo , most studies are in animal models, only a few articles are relevant to human study. In addition, the difference of Al-BMSCs sheet and BMSCs sheet in vitro and the craniofacial bone defect repairment features in vivo remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the regenerated tissues, 24 articles focused on bone , 17 on periodontium 49-65 , 10 on dentin pulp-complex 66-75 and 7 on tooth or tooth root [76][77][78][79][80][81][82] . Regarding bone regeneration, 8 studies developed a porcine model [25][26][27][28][29][30][31][32] , 14 a canine [33][34][35][36][37][38][39][40][41][42][43][44][45][46] and 2 an ovine one 47,48 . Eight studies reported periodontium regeneration in pig [49][50][51][52][53][54][55][56] , 8 in dog [57][58][59][60][61][62][63][64] and 1 in sheep 65 .…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…As control, bone without treatment was taken. The side with the cell sheet was thicker and the bone volume was larger [84].…”
Section: Stem Cells-based Scaffold-free Bone Regenerationmentioning
confidence: 99%